2009
DOI: 10.1111/j.1525-1594.2008.00675.x
|View full text |Cite
|
Sign up to set email alerts
|

Economic, Social, and Psychological Factors Associated With Health‐Related Quality of Life of Chronic Hemodialysis Patients in Northern Taiwan: A Multicenter Study

Abstract: This study evaluated the associations between economic, social, psychological factors, and health-related quality of life of hemodialysis patients. Cross-sectional study design was used. End-stage renal disease patients who had received maintenance hemodialysis for more than 2 months at 14 centers in northern Taiwan were invited to participate. Demographic, economic, and psychosocial data of patients were collected. Depression was assessed by the Beck Depression Inventory. Health-related quality of life was me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
69
4
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(90 citation statements)
references
References 21 publications
9
69
4
8
Order By: Relevance
“…In-depth Review Fleck et al [53] , 2007 Discussion Carver et al [57] , 1995 Review Blinkhorn [61] , 2012 Review O'Connor et al [64] , 2012 Review Catania et al [65] , 2013 Report Quantitative Study design Questionnaire used Mapes et al [8] Longitudinal KDQOLSF-36 Kao et al [13] , 2009 Cross sectional SF-36 Abraham et al [14] , 2008 Case control, follow up WHOQOL-BREF Kimmel et al [15] , 2008 Prospective Satisfaction with Life Scale (SLS), McGill QOL, Single item Patel et al [16] , 2002 Prospective McGill QOL, Beck Depression Griva et al [17] , 2009 Cross sectional SF-36 Elder et al [19] , 2008 Cross sectional, case mix KDQOLSF-36 Sanner et al [20] , 2002 Cross sectional SF-36, Nottingham Health Profile Tondra [22] , 2014 Conceptual Framework, CS Quality of Life Index Dialysis, Mingardi et al [23] , 1999 Prospective SF-36 Seica et al [24] , 2009 Cross sectional SF-36, KDQOLSF-36 Bakewell et al [25] , 2002 Longitudinal /intervention KDQOLSF-36 Theofilou [26] , 2012 Cross sectional/ Observational WHOQOL-BREF, GHQ-28 Kim et al [28] , 2013 Cross sectional KDQOLSF-36 White et al [29] , 2002 Retrospective cohort SF-36 Painter et al [32] , 2000 Experimental/Intervention SF-36 Ouzouni et al [33] , 2009 RCT SF-36, Quality of Life Index Agakhani et al [34] , 2012 Case control/comparative SF-36 Hegazy et al [35] , 2013…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In-depth Review Fleck et al [53] , 2007 Discussion Carver et al [57] , 1995 Review Blinkhorn [61] , 2012 Review O'Connor et al [64] , 2012 Review Catania et al [65] , 2013 Report Quantitative Study design Questionnaire used Mapes et al [8] Longitudinal KDQOLSF-36 Kao et al [13] , 2009 Cross sectional SF-36 Abraham et al [14] , 2008 Case control, follow up WHOQOL-BREF Kimmel et al [15] , 2008 Prospective Satisfaction with Life Scale (SLS), McGill QOL, Single item Patel et al [16] , 2002 Prospective McGill QOL, Beck Depression Griva et al [17] , 2009 Cross sectional SF-36 Elder et al [19] , 2008 Cross sectional, case mix KDQOLSF-36 Sanner et al [20] , 2002 Cross sectional SF-36, Nottingham Health Profile Tondra [22] , 2014 Conceptual Framework, CS Quality of Life Index Dialysis, Mingardi et al [23] , 1999 Prospective SF-36 Seica et al [24] , 2009 Cross sectional SF-36, KDQOLSF-36 Bakewell et al [25] , 2002 Longitudinal /intervention KDQOLSF-36 Theofilou [26] , 2012 Cross sectional/ Observational WHOQOL-BREF, GHQ-28 Kim et al [28] , 2013 Cross sectional KDQOLSF-36 White et al [29] , 2002 Retrospective cohort SF-36 Painter et al [32] , 2000 Experimental/Intervention SF-36 Ouzouni et al [33] , 2009 RCT SF-36, Quality of Life Index Agakhani et al [34] , 2012 Case control/comparative SF-36 Hegazy et al [35] , 2013…”
Section: Resultsmentioning
confidence: 99%
“…[22,25] , influence of dialysis care practice [27] , self-efficacy, treatment satisfaction [28] , pre-dialysis clinic attendance [29] , exercise [30] . Intervention such as dietary counseling [34,35] , individual/group counselling [14,36,37,40] , education on regular exercise [31][32][33] , physical and psychological rehabilitation interventions, palliative care to manage symptoms [38] , and cognitive behavior therapy to reduce depression [39] Inverse association of factors with QOL More worries and higher depression [13] , ignorance about the basic facts of one's disease [14] , Pain, financial constraints [14] , psychological and spiritual factors [15] , emotional impact, physical impact on daily living, role of religious and spiritual beliefs [16] , beliefs related to illness and treatment [17] , anxiety, depression, suicidal ideation, grief of loss of kidney, self-image selfesteem [18] , sleep quality [19] , sleep related breathing disorders [20] , as well as erectile dysfunction, patient satisfaction with care, depressive aspects, symptom burden, and perception of intrusiveness of illness [21] , female gender [22][23][24]26] , ethnicity [25] , older age [26] , less education [24,26] , poor nutritional status [25] and divorced marital status, Illness and treatment beliefs [17] , work and Symptom domain [25] No or very weak association of fa...…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This issue was discussed in another study, but this study demonstrated the positive effects of a supportive family environment, finding that social and family support was one of the most important factors for improving patients' QOL. 41 In conclusion, anxiety and depressive symptoms are prevalent among ESRD patients in Makkah. To the best of our knowledge, this is the first study to screen HD patients for anxiety and depression in Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous studies, 2,[8][9][10]12,13,15,16,18,20,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] we assumed the existence of a 20% difference in the prevalence of depression between the general population and ESRD patients on HD. In order to obtain a confidence level (power) of 95% and a confidence limit of 10%, we aimed to study 246 patients (calculated using the QuesGen Systems sample size calculator).…”
Section: Sample Size Estimationmentioning
confidence: 99%